Cyclical Fluctuations of the Ratio of Bank Loans to Deposits, 1867-1924 - Persons, Warren M. (The Review of Economics and Statistics, 1924)
BOTH the month-to-month fluctuations and the long-time trends of (a) loans and investments, and (b) net deposits of New York Clearing House banks are highly similar. For I903-I3, a period for which the fluctuations were carefully examined in a previous study, the correspondence between the seasonal and cyclical movements of the two series was found to be remarkably close and the slopes of the linear secular trends were shown to be identical.2 The range of fluctuations of the actual figures for net deposits, however, is much wider than that for loans and investments.3 Thus, in years of business depression, such as I904, I908, and I9II, when loans and investments of New York Clearing House banks rose to relatively high levels, it was found that net deposits rose even more. Also, in years of active business, such as I903, I906-07, and I910, when loans and investments declined to low levels, net deposits fell still lower. As a consequence of the lesser range of fluctuations of loans and investments 4 than of net deposits, the ratios of the items of the first series to corresponding items of the second series were found to exhibit marked cyclical movements. Furthermore, the timing and general contour of the cyclical movements of the curve representing the loan-deposit ratio were found to agree closely with those of the curve representing rates on commercial paper adjusted for seasonal influences. This agreement, for the ten or eleven years preceding the war, is evident from the comparison in Chart 2 of the loan-deposit ratio and rates on commercial paper.5 Thus the process of taking the ratio of loans and investments to net deposits of New York Clearing House banks results in a series fluctuating concurrently with money rates and, at least for the decade preceding the war, furnishes a supplementary index of money conditions. The crests and the troughs of the cyclical fluctuations of the loandeposit ratio, it should be noted, come at quite different times from those of the constituents of the ratio. That is, the trough of the curve for ratios comes in times of business depression and the early stages of business recovery, when the curves for loans and investments and net deposits of New York Clearing House banks are high; the crest of the curve for ratios comes in times of business prosperity and financial strain, when the curves for loans and investments and net deposits are low. The object of the present study is to ascertain if the loan-deposit ratio (or possibly, the loanliability ratio) is an accurate index of money conditions for other periods than the decade preceding the war and for other banks than those belonging to the New York Clearing House. The reason for studying the ratio of loans and investments to deposits (or, the ratio of loans and investments to total liabilities) rather than the individual series of loans and investments by itself is threefold. First, as stated above, the loan-deposit ratio furnished an accurate index